Alcoholic Fractions F5 and F6 from Withania somnifera Leaves Show a Potent Antileishmanial and Immunomodulatory Activities to Control Experimental Visceral Leishmaniasis - Chandrasekaran, Sambamurthy; Veronica, Jalaja; Sundar, Shyam; Maurya, Radheshyam (Frontiers in Medicine, 2017)
Visceral Leishmaniasis (VL) causes fatal life threatening disease, if left untreated. The current drugs have various limitations; hence, natural products from medicinal plants are being focused in search of new drugs to treat leishmaniasis. The aim of present study was to evaluate the alcoholic fractions of F5, F6 from W. somnifera leaves and purified Withaferin-A as antileishmanial & immunomodulatory activities in L. donovani infected peritoneal macrophages and BALB/c mice. We observed that F5 (15μg/ml), F6 (10μg/ml) and Withaferin-A (1.5μM) reduce amastigote count in peritoneal macrophages, induced reactive oxygen species and significant decrease in IL-10 mRNA expression compared to control upon treatment. Subsequently, in-vivo study mice treated with F5 (25mg & 50mg/kg b.wt), F6 (25mg & 50mg/kg b.wt) orally and Withaferin-A (2mg/kg b.wt) intraperitoneally for 10 consecutive days and observed a drastic reduction in parasite burden in both spleen and liver. The treatment resulted in the reduction IL-10, IL-4, and TGF-β mRNA expression and a significant increase of IFN-γ/IL-10 expression ratio in the treated group compared to control. The humoral response of these alcoholic fractions and Withaferin-A show increased IgG2a levels as compared to IgG1 in treated mice. Taken together our result concludes that withanolides in alcoholic fractions demonstrate a potent antileishmanial and immunomodulatory activities in experimental VL.